2021
DOI: 10.1371/journal.pone.0256066
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-1202 promotes the TGF-β1-induced proliferation, differentiation and collagen production of cardiac fibroblasts by targeting nNOS

Abstract: Background Atrial fibrillation (AF) is a clinically common arrhythmia that affects human health. Myocardial fibrosis serves as an important contributor to AF. Recently, miRNA-1202 have been reported to be up-regulated in AF. However, the role of miRNA-1202 and its mechanism in myocardial fibrosis remain unclear. Methods Human cardiac fibroblasts (HCFs) were used to construct a fibrosis model by TGF-β1 induction. The expression of miR-1202 was measured by qRT-PCR. Cell proliferation was assessed by CCK-8 assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…But increasing the expression of miR-376b-3p, on the contrary, inhibits the proliferation of fibroblasts, causing their premature aging [53]. miR-1202 promotes fibrosis by inducing TGF-β1 [54]. According to our assumptions, chrysotile asbestos could cause changes in the expression of these microRNAs.…”
Section: Discussionmentioning
confidence: 77%
“…But increasing the expression of miR-376b-3p, on the contrary, inhibits the proliferation of fibroblasts, causing their premature aging [53]. miR-1202 promotes fibrosis by inducing TGF-β1 [54]. According to our assumptions, chrysotile asbestos could cause changes in the expression of these microRNAs.…”
Section: Discussionmentioning
confidence: 77%
“…TGF-β induces collagen deposition in the ECM, and some miRNAs inhibit collagen production by regulating the TGF-β/Smad signaling pathway, thereby inhibiting ECM deposition, and alleviating cardiac fibrosis. Xiao et al ( Xiao et al, 2021 ) discovered that miR-1202 promoted the proliferation, differentiation, and collagen synthesis of HCFs by activating the TGF-β1/Smad2/3 signaling pathway, and downregulated the nNOS by binding to target sites in its mRNA. While, nNOS protected HCFs from TGF-β1-induced differentiation and collagen synthesis via the TGF-β1/Smad2/3 pathway.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%
“… 30 Other studies also demonstrated that miR-21 targeted Smad7, 31 miR-29b targeted TGF-βRI, 32 miR-135b targeted TGF-βRI, TGFβ-RII, and Smad2, 33 and miR-23b-3p and miR-27b-3p targeted two different sites in 3'-UTR of TGF-βRIII to participate in atrial fibrosis ( Table 1 ). 34 Additionally, miRNAs have been observed to target molecules linked with TGF-β1 signalling pathway, such as hsa-miR-4443 targeted THBS1, 35 miRNA-1202 targeted nNOS, 36 and miR-21 regulated WW domain-containing protein 1 ( Table 1 ). 37 All of these indicated that miRNAs associated with TGF-β1/Smads signalling may be attractive therapeutic targets, and future studies are needed to further explore whether these miRNAs can be used to develop new drugs, thereby achieving clinical translation.…”
Section: Mirnas and Arrhythmiasmentioning
confidence: 99%